Investing in the agri-food system for post-COVID-19 recovery: An economywide evaluation of public investments in Egypt - Thurlow, James; Holtemeyer, Brian; Kassim, Yumna; Kurdi, Sikandra; Randriamamonjy, Josee; Raouf, Mariam; Elsabbagh, Dalia; Wiebelt, Manfred; Breisinger, Clemens (International Food Policy Research Institute, 2020)
This note presents the results of an evaluation of public investment options for Egypt’s agri-food system. Nine agriculture-related public investments are considered, including targeting public spending to expand farm production, e.g., irrigation improvements, input subsidies, agricultural research, and extension, and to promote downstream agro-processing and marketing. The outcome indicators considered are economic (GDP) growth, incomes of the poor, job creation, and dietary diversity. IFPRI’s Rural Investment and Policy Analysis (RIAPA) economywide model is used for the evaluation because it captures linkages between sectors, households, and rural-urban economies and measures changes within and beyond the agri-food system. RIAPA is linked to the Agricultural Investment and Data Analysis (AIDA) module that tracks investment impacts and costs over time. The ranked results of the public investment options considered, summarized in the table here, can help prioritize agri-food system investments for post-COVID-19 recovery.